A Selected Bibliography on Mexican American and Native American Bilingual Education in the Southwest (With ERIC Abstracts). CAL. ERIC CLL Series on Languages and Linguistics, No. 6 / Stephen Cahir and Others. - Cahir, Stephen (Distributed by ERIC Clearinghouse, 1975)
This bibliography provides access to the latest research findings or developments in bilingual education which relate specifically to Mexican Americans and/or American Indians in the Southwest. The information contained in the 263 entries is analyzed within similar limits as to its sociolinguistic significance. Compiled from abstracts which appeared in the January 1971 thru June 1974 issues of "Research in Education" (RIE), the bibliography consists of three sections: (1) an analysis of individual entries in terms of their sociolinguistic significance; (2) the ERIC abstracts in numerical order; and (3) a subject index. Topics emphasized are biculturalism, bilingualism, content analysis, English as a second language, program evaluation, and Spanish. Entries cover a wide variety of educational materials such as research reports, program descriptions and evaluations, and resource materials. Ordering information is appended. (NQ)